Student experience of intergroup contact at IIUM - Afzal, Sofia (Kuliyyah of Education, International Islamic University Malaysia, 2017)
Although the intergroup contact hypothesis was proposed in early twentieth century and multitudes of research have been conducted in various educational institutions, barely any have studied it in the Muslim-Muslim interaction or from a phenomenological approach. This research attempts to investigate the experience of intergroup interaction at International Islamic University Malaysia (IIUM) and to decipher the role of the university and its Islamic identity among three Malay and three international students at IIUM, Gombak. The analysis of the phenomenological interview showed that both groups generally had a pleasant experience. English language proficiency was highlighted as it was the bridge for communication. The importance of language thus underlined the role of IIUM's pre-university language centre in facilitating intergroup interaction. The university played a vital part in the contact as the most effective venues for contact was the classroom which, in many cases, provided Allport's conditions for successful prejudice reduction. On the other hand, the concept and implementation mixed residences need to be improved as it was seen as most detrimental to intergroup contact. The analysis gave an insight into the Islamization and Internationalization efforts of the university and drew implications for the intergroup contact theory. Suggestions to improve contact have also been put forth.